Individual differences in susceptibility to large portion sizes among obese and normal‐weight children. (13th February 2015) - Mooreville, Mira; Davey, Adam; Orloski, Alexandria; Hannah, Elizabeth L.; Mathias, Kevin C.; Birch, Leann L.; Kral, Tanja V.E.; Zakeri, Issa F.; Fisher, Jennifer O.
Abstract : Objective: Determine the association of children's susceptibility to large food portion sizes with appetite regulation and obesity. Methods: Normal‐weight and obese non‐Hispanic black children ( n = 100) aged 5‐6 years were observed in four dinner conditions of varying portion size; portions of all foods (except milk) offered were: 100% (677 kcal), 150% (1015 kcal), 200% (1353 kcal), or 250% (1691 kcal) of those in the reference condition (100%). Condition order was randomly assigned to 2‐4 children who ate together at each meal. Child height and weight were measured and caregiver reports of child appetite were obtained. Hierarchical growth curve models were used to estimate associations of meal energy intake with portion size condition, child weight status, and appetite regulation traits, controlling for demographics. Results: Total energy intake increased across conditions of increasing food portion size ( P < 0.001). The effect of portion size condition on total energy intake varied with food responsiveness ( P = 0.05) and satiety responsiveness ( P < 0.05), but not weight status ( P = 0.682). Children with lower satiety responsiveness and greater food responsiveness showed greater increases in meal energy across conditions. Conclusions: Children with poorer appetite regulation may be more vulnerable to obesogenic dietary environments offering large food portions than other children.